PENERAPAN MODEL PROJECT BASED LEARNING TERINTEGRASI TPACK PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Siti Handayani; Heri Maria Zulfiati; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Project Based Learning learning model and the TPACK concept and its application to learning in schools will have a positive impact on science and science learning in elementary schools. In practice, teachers are not used to using this method but are used to using traditional student center learning. This research aims to describe the application of Project Based Learning with the TPACK approach in science and science learning for class V at SD Negeri 3 Karangwuni. In this application, the teacher acts as a facilitator and companion for students in carrying out the project, while students act as active learners who look for solutions to the challenges given. In this case the researcher uses a descriptive qualitative research method with a phenomenological type of research which will describe the process of implementing learning. Data collection techniques include observation, interviews, giving tests and documentation. The results of the research show that the implementation of the Project Based Learning model with the TPACK approach in science and science learning in class 5 of SD Negeri 3 Karangwuni has gone well and is in accordance with the school's vision and mission. The positive impact is that learning becomes more interesting, improves students' academic and non-academic achievements, learning is not boring, and teachers are more creative.